A New Generation of Primary Luminescent Thermometers Based on Silicon Nanoparticles and Operating in Different Media - Botas, Alexandre M. P.
Luminescence nanothermometry is nowadays a highly-dynamic research topic that is being driven by the challenging demands arising from dissimilar areas such as microelectronics, microfluidics and nanomedicine. Although the technique is rapidly evolving from the initial breakthrough to real applications, there are still major challenges regarding the conciliation of nanometric probes with the high sensitivity and predictability of the thermal response of the system. In the past five years, luminescent thermometers operating at the nanoscale, where the conventional methods are ineffective, have emerged as a very active field of research. Luminescent silicon nanoparticles (SiNPs) are a promising choice for nanothermometry, combining the Si biocompatibility with the compatibility with the current microelectronic technology. Here, the thermal dependence of the emission peak position of SiNPs, used as the thermometric parameter, is well-described by the Varshni's law, enabling the development of a self-calibrated nanothermometer with a calibration curve predicted by a well-stablished state equation, avoiding new calibration procedures whenever the thermometer operates in different media. For the first time, temperature sensing using SiNPs-based luminescent thermometers in different media without the need of new calibration procedures is demonstrated. The thermometer reveals reversibility and repeatability higher than 99.98%, and a maximum relative sensitivity of 0.04% K-1.